Characteristics of homologous recombination repair pathway genes mutation in ovarian cancers. Issue 3 (20th September 2022) - Yi, Zongbi; Chen, Min; Sun, Shaoxing; Yang, Chunxu; Mei, Zijie; Yang, Hui; Xiang, Qingming; Qiu, Hui
Abstract: Background: Few studies have investigated the characteristics of non‐ BRCA homologous recombination repair (HRR) pathway somatic mutations, and the impact of these mutations on efficacy of treatment in ovarian cancer patients is not clear. Therefore, we conducted this study to analyze the frequency and spectrum of somatic mutations in HRR pathway genes in patients with ovarian cancer and to examine the relationships between somatic mutations in HRR pathway genes and their effects on the efficacy of platinum‐based chemotherapy. Methods: We performed targeted sequencing of 688 genes related to the occurrence, development, treatment, and prognosis of solid tumors. Somatic mutations were identified by paired analysis of tumor tissue and germline DNA in blood cells. Results: A total of 38 patients with ovarian cancer were included in the study, and 35 (92.1%) patients were diagnosed with high‐grade serous carcinoma. All patients exhibited somatic mutations in the tumor tissue samples. The commonly mutated genes were TP53 (73.7%), BRCA2 (55.3%), NF1 (52.6%), BRCA1 (47.4%), and CDH1 (47.4%). Overall, 71.1% of the patients exhibited mutation in at least one HRR pathway gene. The most frequently altered HRR genes were BRCA2 (55.3%), followed by BRCA1 (47.4%), ATM (44.7%), BARD1 (42.1%), and CHEK1 (36.8%). The median progression‐free survival (PFS) in patients with HRR pathway mutation was 36.0 months compared with 13.6 months in patients with no HRR pathway mutation (hazard ratio [HR], 0.25; 95% confidence interval [CI], 0.08–0.77; p = 0.016). Patients harboring BRCA1/2 and/or CDK12 mutations displayed a longer PFS (median, 36.0 months) compared with patients with no BRCA1/2 or CDK12 mutation (median, 13.6 months; HR, 0.21; 95% CI, 0.07–0.61; p = 0.004). In multivariate analysis Cox proportional hazards models, after adjustment for tumor stage at diagnosis and histology of initial diagnosis, patients with HRR pathway mutation had a longer PFS than patients with HRR wild‐type genes ( p = 0.006). Conclusions: HRR pathway somatic mutations are common in Chinese patients with ovarian cancer. HRR pathway somatic mutations were associated with improved sensitivity to platinum‐based chemotherapy. Large‐scale prospective studies are needed to verify our findings. Abstract : This study analyzed the spectrum of somatic mutations in homologous recombination repair (HRR) pathway genes in patients with ovarian cancer and examined the relationships between somatic mutations in HRR pathway genes and their effects on the efficacy of platinum‐based chemotherapy. The results revealed that HRR pathway somatic mutations are common in Chinese patients with ovarian cancer and associated with improved sensitivity to platinum‐based chemotherapy.